Overdiagnosis in Colorectal Cancer Screening - Time to Acknowledge A Blind Spot - Kalager, Mette; Wieszczy, Paulina; Lansdorp-Vogelaar, Iris; Corley, Douglas A; Bretthauer, Michael; Kaminski, Michal F (Gastroenterology (New York, N.Y. 1943), 2018)
Overdiagnosis is recognized as a major harm of mammography screening for breast cancer and prostate cancer screening with prostate-specific-antigen (PSA). Colorectal cancer screening is being more broadly implemented in many countries, and screening rates are increasing steadily. Surprisingly, there is a striking and almost complete lack of knowledge about overdiagnosis in colorectal cancer screening. Overdiagnosis is not part of patient information material, hardly mentioned in guidelines, and not addressed in scientific or public debate. The present paper proposes a semantic, conceptual and clinical framework for overdiagnosis in CRC screening.